CARTOGRAPHY OF A TRANSLATION COMMENTARY - Escalante, Alba (Revista de Letras, 2023)
To widen reflections on research in Translation Studies, this paper proposes annotated translation as a cartographic writing of the translation zone. The territory is the translation of psychoanalytical theories. The translation zone follows the trail of clues left in situations where the term immixing, referring to the subject of the unconscious, is presented in Jacques Lacan's theory. We work with the translations of this term starting from its presentation in the 1966 lecture: Of structure as an immixing of an otherness prerequisite to any subject whatever. We go through other places in Lacan's translations where the term appears. We arrive at productions of Latin American psychoanalysts linked to his work. We sense that, at the time of the so-called Baltimore Conference, Lacan chose to mix languages, pointing out the potential of translation. In our tracks, the languages of translation present the force of multiplicity. These signs of deterritorialization cease when, through translation, the institutional form stabilizes the utterances.